Efficient ultraviolet photodetectors based on TiO2 nanotube arrays with tailored structures. Issue 65 (16th July 2015) - Wang, Lianbo; Yang, Weiyou; Chong, Haining; Wang, Lin; Gao, Fengmei; Tian, Linhai; Yang, Zuobao
<x xml:space="preserve">Abstract</x> We report the front-illuminated ultraviolet photodetectors based on TiO2 nanotube arrays with efficient photodetecting activities.